2012
DOI: 10.1007/s00428-012-1302-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of emmprin and monocarboxylate transporter-1 in ovarian epithelial tumors

Abstract: Emmprin is a transmembrane glycoprotein known as a matrix metalloproteinase inducer and is highly up-regulated in malignant cancer cells. The monocarboxylate transporters (MCTs) are responsible for H(+)-linked transport of monocarboxylates across the cell membrane. It was recently demonstrated that proper plasma membrane localization and activity of MCTs require the presence of emmprin as a chaperone and that MCT-1 also acts as chaperone for emmprin. The objectives of this study were to clarify emmprin and MCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
6
0
4
Order By: Relevance
“…Importantly, its expression is often correlated with tumor metastasis and poor prognosis [10-18]. There are already papers showing that basigin is associated with the survival and progression of ovarian cancer, and is considered as a biomarker of poor outcome [39-41]. However, some results show that basigin is a significant indicator of a favorable prognosis of ovarian cancer [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, its expression is often correlated with tumor metastasis and poor prognosis [10-18]. There are already papers showing that basigin is associated with the survival and progression of ovarian cancer, and is considered as a biomarker of poor outcome [39-41]. However, some results show that basigin is a significant indicator of a favorable prognosis of ovarian cancer [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CD147 expression is often concurrent with other factors involved in the pathological process, such as MCTs. Good colocalization of CD147 and MCT1 has been found in 23 carcinomas by identical immunostaining scores [9]. Furthermore, an immunohistochemical examination of the plasma membranes of MLS-175 soft tissue sarcoma cells revealed that 40% of samples were positive for CD147 and 60% were positive for MCTs (MCT1 and MCT4) [55].…”
Section: The Expression and Role Of Cd147 In Tumor Cellsmentioning
confidence: 99%
“…Many different human cancers over-express CD147 on tumor cell surfaces, including several common cancers (Table 1) and giant cell tumors [49], synoviocytes [50], cancer stem cells (CSCs) [51], and human multiple myeloma cell lines (HMCLs) [52]. Other investigators have found that CD147 is expressed in the membranous and/or cytoplasmic compartments of ovarian carcinoma [9,53]. Moreover, the CD147 expression level is not related to the age of the cancer patient, tumor type or gross morphology but is related to tumor histopathologic type and clinical stage of disease [52,54].…”
Section: The Expression and Role Of Cd147 In Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCTs are responsible for H + -linked transport of monocarboxylates across the cell membrane. It was recently demonstrated that proper plasma membrane localization and activity of MCTs require the presence of EMMPRIN as a chaperone and that MCT-1 acts as chaperone for EMMPRIN [45]. Indeed, this study showed that silencing of EMMPRIN decreased MCT1 expression and abolished the co-localization of EMMPRIN and MCT1.…”
Section: Discussionmentioning
confidence: 69%